Highly Efficient and Biologically Compatible Photoremovable Protecting Group for Releasing Tertiary Amines through Two‐Photon Excitation. Issue 1 (1st October 2022) - Asad, Naeem; Deodato, Davide; Gore, Sangram; Dore, Timothy M.
Abstract: Photoremovable protecting groups (PPGs) releasable by two‐photon excitation (2PE) provide spatio‐temporal control over the photoactivation of biological effectors to study biological systems. We synthesized four derivatives of the (8‐cyano‐7‐hydroxyquinolin‐2‐yl)methyl (CyHQ) chromophore by functionalization of position C4 to generate four different derivatives (MeO‐CyHQ, Mor‐CyHQ, p Tol‐CyHQ, and TMP‐CyHQ) for studying the release of tertiary amines via 2PE. Sulpiride, an anti‐dopaminergic drug, was selected as a model substrate. All probes had excellent properties for use in biological settings, including high quantum yield (Φu ), hydrolytic stability, and good aqueous solubility in simulated physiological buffer. The TMP‐CyHQ probe enhanced the two‐photon uncaging action cross‐section (δu ) 8‐fold (2.64 GM) compared to the parent CyHQ‐sulpiride. The optimized PPG was used to mediate the photoactivation of various biological effectors containing the tertiary amine functionality (tamoxifen, 4‐hydroxytamoxifen, yohimbine) using 2PE. All constructs showed excellent efficiency with δu ranging from 1.21 to 2.42 GM and moderate to excellent yields of tertiary amines released. Abstract : Let it go : Four (8‐cyano‐7‐hydroxyquinolin‐2‐yl)methyl (CyHQ)‐based photoremovable protecting groups (PPGs) were synthesized to study the release of tertiary amines though one‐ and two‐photon excitation (1PE, 2PE). The 3, 4, 5‐trimethoxyphenyl derivative (TMP‐CyHQ) released tertiary amines with the highest 1PE quantum efficiency and 2PE uncaging action cross section. TMP‐CyHQ successfully released sulpiride, tamoxifen, 4‐hydroxytamoxifen, yohimbine, triethylamine, and N‐methylmorpholine through 1PE and 2PE (Φu =0.22–0.78 and δu =1.21–2.42 GM).